Heterodispus cordidiscus n. sp., a new soil mite from Egypt, and remarks on the nominal species H. elongatus Trägårdh, 1905 (Acari: Heterostigmatina: Scutacaridae) - Jagersbacher-Baumann, Julia; Ebermann, Ernst (Zootaxa, 2012)
The description of a new Egyptian soil inhabiting scutacarid species, Heterodispus cordidiscus n. sp. (Acari, Heterostig-matina), including female, male and larva, is given. It is the first description of male and larva within the genus Hetero-dispus Paoli, 1911. The redescription of the nominal species H. elongatus Trägårdh, 1905 by Paoli (1911) has beenerroneous and we now show that the redescription made by Mahunka (1963) does not describe H. elongatus, either. Theincorrectly interpreted species is hereby provided with the new name H. pannonicus n. nom.. A corrigendum for the setal formula of leg I of H. foveatus Jagersbacher-Baumann and Ebermann, 2012 is given.